Origin of matter & evolution of galaxies 2003 (World Scientific, 2005)
This is the proceedings of the International Symposium on Origin of Matter and Evolution of Galaxies which was held near Tokyo, Japan, in November 2003. The meeting brought together many scientists from vast fields — nuclear physics, particle physics, cosmic-ray physics, cosmology, astronomy, geophysics, and others